Building applications with Windows Workflow Foundation (WF) : advanced workflow features - Stiefel, Michael (Short cuts on Windows workflow., 2007)
Windows Workflow Foundation (WF) is Microsoft's programming model for building workflow-enabled applications in the Windows operating system. It includes a namespace, a workflow engine, and design tools that can be used with Visual Studio .NET. Workflow is an extremely important type of application that has been difficult to build on the Microsoft platform. Workflow Foundation is a major element of the .NET Framework 3.0 platform that enables application developers to build these types of applications. In Building Applications with Windows Workflow Foundation: Advanced Workflow Features, author, MVP, speaker, and leading consultant Michael Stiefel introduces readers to the some of the more advanced features of Windows Workflow foundation that are necessary for building more sophisticated applications.